(untitled) (World Bulletin of Management and Law, 2025)
This article examines the legal status of children in the national and international legal systems. Particular attention is paid to the analysis of international documents, primarily the UN Convention on the Rights of the Child, and their influence on the formation of national legislation. The author examines the peculiarities of legal regulation of children’s rights in various jurisdictions, identifies problems in the implementation of international standards at the national level, and assesses the effectiveness of existing protection mechanisms. The article emphasizes that ensuring children’s rights requires not only legislative consolidation, but also the effective functioning of institutions capable of guaranteeing the observance of these rights. The conclusion is made about the need to strengthen cooperation between international and national structures in order to improve the level of legal protection of children